Development of Conceptual Change-Based Worksheets to Reduce Misconceptions in Chemical Bonding - Dhafa Ayu Sheilamita; Bertha Yonata (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2026)
This study aims to analyze the feasibility of conceptual change-based student worksheets (SWs) to reduce misconceptions in chemical bonding material. The study used the Borg and Gall Research and Development (R&D) model. A limited trial was conducted on 25 students of SMAN 19 Surabaya. The research instruments included a validation sheet, a student response questionnaire, an activity observation sheet, and a four-tier diagnostic test. The results showed that content and construct validation obtained a mode of 5 with a very good category. The practicality of the SWs was demonstrated by the percentage of student responses of 94% and student activity of 96.54% with a very practical category. Effectiveness was demonstrated by the percentage of positive conceptual shifts of 93% with a very effective category. Based on these results, the SWs was declared valid, practical, and effective in reducing student misconceptions and can be used as an alternative teaching material on chemical bonding material.